2014
DOI: 10.1002/2013jc009614
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mesoscale activity in the Solomon Sea: A complementary approach with a numerical model and altimetric data

Abstract: The Solomon Sea is an area of high level of eddy kinetic energy (EKE), and represents a transit area for the low-latitude western boundary currents (LLWBCs) connecting the subtropics to the equatorial Pacific and playing a major role in ENSO dynamics. This study aims at documenting the surface mesoscale activity in the Solomon Sea for the first time. Our analysis is based on the joint analysis of altimetric data and outputs from a 1/12 model simulation. The highest surface EKE is observed in the northern part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 67 publications
2
43
0
Order By: Relevance
“…Using DT instead of MSLA data is beneficial to consistently compare altimetric observations with the absolute information from glider data and from the modeled Sea Surface Height (SSH). Although it is challenging to produce a high‐quality mean dynamic topography product in this complex region, it compares well with the time‐averaged modeled SSH (not shown), and the DT fields have been successfully used to explore the surface mesoscale activity in the Solomon Sea (Gourdeau et al, ).…”
Section: Data Model and Eddy Identificationmentioning
confidence: 91%
See 1 more Smart Citation
“…Using DT instead of MSLA data is beneficial to consistently compare altimetric observations with the absolute information from glider data and from the modeled Sea Surface Height (SSH). Although it is challenging to produce a high‐quality mean dynamic topography product in this complex region, it compares well with the time‐averaged modeled SSH (not shown), and the DT fields have been successfully used to explore the surface mesoscale activity in the Solomon Sea (Gourdeau et al, ).…”
Section: Data Model and Eddy Identificationmentioning
confidence: 91%
“…The Solomon Sea is an area of high eddy kinetic energy (EKE), and surface mesoscale vortices have been studied by a complementary approach using a numerical model and altimetric data (Gourdeau et al, ). In this study, mesoscale activity in the Solomon Sea was found to be mainly generated by instabilities of the regional large‐scale currents, and their modulation at seasonal and interannual timescales to be highly related to the intrusion of the SSI that modulates the vertical and horizontal shears suitable for instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The coastal current vein is 120 km wide east of Vitiaz Strait (track 099) and 100–200 km west of the strait (Figure b). It is the widest (near 200 km) along tracks 023 and 201 in agreement with the surface current issued from the 1/12° Ocean General Circulation Model (OGCM) [ Delcroix et al ., ] developed by the DRAKKAR group [ Gourdeau et al ., ]. A southwestward flow entering the Bismarck Sea between Manus Island and New Ireland merges with the along‐coast current at this location in winter.…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…The southeastward coastal current in the west and the northwestward flow exiting from Vitiaz Strait create a convergence near the Sepik River mouth. This convergence is reproduced in the OGCM for the Earth Simulator (OFES) simulation [ Hasegawa et al ., ] and in the DRAKKAR 1/12° OGCM [ Gourdeau et al ., ] where it generates an offshore flow [ Hasegawa et al ., ; Delcroix et al ., ] that shapes the surface chlorophyll pattern off the Sepik River (Figure d).…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…The VOS‐derived and model‐derived SST and SSS monthly climatology presented along the mean‐shipping track in Figure present a very good correspondence, giving us extra confidence in the already‐evaluated model outputs [ Gourdeau et al ., ]. Two month averaged maps of modeled SST and SSS are then shown in Figures and , together with the corresponding absolute surface current field, to replace the along‐track monthly climatology in a larger regional context.…”
Section: Sss and Sst Seasonal Changesmentioning
confidence: 99%